How to extend value-based healthcare to population-based healthcare systems? Defining an outcome-based segmentation model for health authority - Torkki Paulus; Leskelä Riikka-Leena; Mustonen Pirjo; Linna Miika; Lillrank Paul (BMJ Publishing Group, 2025)
Objectives Value-based healthcare (VBHC) is considered the most promising guiding principle for a new generation of health service production. Many countries have attempted to apply VBHC to managerial and clinical decision-making. However, implementation remains in its infancy and varies between countries. The objective of the study is to help health systems implement a value-based approach by building an outcome-based population segmentation model for health authorities (HAs).
Design First, we define the principles according to which segmentation models in healthcare could be developed. Second, we merge the theoretical characteristics of outcomes with population segmentation dimensions identified in previous literature and design a flow model that establishes population segments from these combinations. We then estimate the size of the segments based on national register data.
Results The population can be divided into 10 different segments based on relevant outcomes, goals and the outcome measurement logic. These segments consist of healthy, help, increased risk, mild curable without risk, mild curable with risk, severe curable without risk, severe curable with risk, single chronic, multimorbid and terminal. The representatives of Finnish HAs found the segments meaningful for evaluating and managing the healthcare system towards improved population health.
Conclusions An outcome-based segmentation model for the entire population is needed if an HA wants to steer the healthcare system employing the principles of VBHC. Segmentation should be based on the outcome measurement logic and outcome measurements relevant to each segment and the number of segments has to be limited.